Politicization and Regional Integration in Latin America: Implications for EU–MERCOSUR Negotiations? - Andrea C. Bianculli (Politics and Governance, 2020)
Regional integration in Latin America has experienced different periods of politicization. The most recent goes back to the 2000s and is related to the domestic political changes resulting from the so-called ‘left turn’ which sought alternative economic and development policies to neoliberalism as the state regained centrality. These transformations led to a broad process of politicization of regionalism which changed the terms of the debate surrounding whether regional integration and free trade are the only way for these countries to integrate regionally and internationally. Analyses have thus underscored the postliberal character of this phase of regionalism as reflected in the greater weight of social and political agendas at the expense of economic and trade issues. The Common Market of the South (MERCOSUR) was no exception to this trend. However, in 2010 the bloc rather surprisingly agreed to relaunch negotiations with the European Union (EU). Why did MERCOSUR decide to resume these negotiations—stalled since 2004—in a context of high politicization of regional integration? This article argues that internal politicization did not lead to a paralysis of the international agenda. Moreover, internal politicization, coupled with external pressures and the demand for group-to-group negotiations by the EU, drove and supported the conduct of international negotiations. In so doing, this article also contests the idea that after the 2000s, MERCOSUR moved inexorably towards a postliberal model, thus rejecting any trade component. Findings suggest that these accounts may have overemphasized change and underestimated continuities in regional integration dynamics as the case of the external agenda shows.